Beyond water data: benefits to volunteers and to local water from a citizen science program. Issue 2 (28th January 2019) - Church, Sarah P.; Payne, Lindsey B.; Peel, Sara; Prokopy, Linda S.
Abstract : Survey results of citizen science water data collection volunteers are presented, indicating personal benefits (e.g., being in nature, helping local water quality), and suggesting potential long-term benefits of improved watershed health (e.g., behavior change). These results can inform citizen science program development and contribute to watershed planners' understanding of the broad benefits of such programs. We suggest that respondents' positive feelings toward the watershed's major river and desire to learn about science and nature are place-specific elements that watershed and citizen science program managers could utilize in program development. Moreover, we explore the potential of social diffusion and behavior change and suggest the need for further research in these areas. We conclude that citizen science has potential not just as a means to collect large amounts of data (cheaply), but as a means to engage citizens to make environmentally friendly decisions.